Addressing Ethical Challenges Related to Community and Patient Engagement in Health Research - Cordeaux, Emily; Sheikhan, Natasha; Boateng, Rhonda (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2024)
In this post-workshop summary, we describe three ethical challenges related to engaging people with lived experience as partners in health research. We share learnings and reflective prompts from our workshop delivered as part of the Canadian Bioethics Society Workshop and Community Forum held in May 2023.